THE INFLUENCE OF COOPERATION PRINCIPLE FOR THE VIOLATIONS OF POLITENESS PRINCIPLE IN THE MOVIE TENGGELAMNYA KAPAL VAN DER WIJCK (PENGARUH PRINSIP KERJA SAMA TERHADAP PELANGGARAN PRINSIP KESANTUNAN DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK) - Nadiatul Khairiah; Ike Revita; Rina Marnita (Universitas PGRI Sumatera Barat, 2020)
The principle of conversation is an important part of communication, both the cooperation principle and the politeness principle. Cooperation principle is consideribly necessary to make the point of communication is delivered properly, so it doesn’t make any reinterpretation. On the other hand, politeness principle is important to keep social relation among the speakers. This research discusses the influence of the cooperation principle on violations that occur in the politeness principle. Data are utterances found in the movie Tenggelamnya Kapal Van der Wijck. This study is worthed to conduct due to in the Tenggelamnya Kapal Van der Wijck film, it is found many cause and effect relationships between the cooperation and politeness principle. The purpose of this research is to describe the relationship between the two principles. At the stage of providing data, the writer used the refer method. The data analysis phase is used by the equivalent method by utilizing the intralingual and extralingual equivalent methods. The results of data analysis are presented descriptively and assisted with the use of tables. The results of the study show that, between the two principles the conversation does not always support each other. However, an effort was found to fulfill a principle by violating other principles, in other words there was a correlation between the two principles. Based on the analysis carried out, it was found that there were several utterances that violated the politeness principle influenced by the cooperation principle that was fulfilled. The factor behind this is the tendency of the participants to say clearly and frankly even though they must override the politeness principle.